Cocaine trafficking in Latin America : EU and US policy responses - Fukumi, Sayaka, 1973- (Global security in a changing world, 2008)
"The European Union and the United States have identified Latin American cocaine trafficking as a security threat, but their policy responses to it have differed. This book examines the way in which the EU and US have conceptualized this threat. Furthermore, it explores the impact of cocaine trafficking on four state functions: economic, political, public order, and diplomatic, in order to explain why it has become 'securitized'."--BOOK JACKET.